Digital Madrasah: Empowering Technology Literacy for Teachers - Subhan Ajrin Sudirman; Muhammad Naufan Rizqullah; Novia Lestari; Yuharnida Yuharnida; Bagus Pribadi; Rahman Pranovri Putra (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
The digital transformation of madrasahs has become imperative in the current digital era to address the evolving challenges of educational relevance. The digitalization process in madrasahs, particularly at MAN 3 Tanah Datar, encounters several obstacles, including limitations in infrastructure and human resources. Through the Science and Technology Literacy initiative spearheaded by the Faculty of Science and Technology at UIN Imam Bonjol Padang, this community service activity aims to strengthen technology literacy among teachers at MAN 3 Tanah Datar. The initiative includes training on the use of digital media creation and assessment applications, such as Canva, Quizizz, and Wordwall. The methodology employed encompasses three phases: pre-implementation, implementation, and post-implementation. The outcomes indicate that the training successfully enhanced teachers' technological skills, which in turn contributed to creativity and innovation in teaching and learning processes. Monitoring and evaluation activities showed that the use of Canva, Wordwall, and Quizizz at MAN 3 Tanah Datar increased student engagement and motivation, but there is still a need for media adaptation to accommodate a variety of learning styles. Continued efforts in digitalization are necessary to realize the full potential of a digital madrasah. Technology-based training programs like these are expected to bolster the madrasah's human resources, equipping them to meet global challenges in the digital age. Keywords: digital madrasah; technology literacy; teacher